The Perception of Millennial Generation on Religious Moderation through Social Media in the Digital Era - Suci Ramadhanti Febriani; Apri Wardana Ritonga (Millah: Journal of Religious Studies, 2022)
The phenomenon of learning religion through social media is rife among the millennial generation. This is an opportunity for the internalization of religious moderation in the millennial environment. This study aims to reveal the millennial generation's perception of religious moderation through social media. This study uses a qualitative research design with case study methods, while data collection techniques include interviews, observation, and documentation integrally with data analysis techniques through the theory of Milles and Huberman. This study shows that the millennial generation's perception of the implementation of religious moderation can be internalized through social media intermediaries with video, reading articles, and intensive persuasion strategies from social media content owners. The research findings illustrate that the phenomenon of the implementation of religious moderation in the millennial generation can be improved through the distribution of religious materials that are relevant to modern issues without reducing the essence of religious education. This study recommends further research to examine the effectiveness of understanding religious moderation in the younger generation in dealing with pluralism in Indonesia.